UPAYA PENGUATAN LITERASI INFORMASI DAN KOMUNIKASI INTERNASIONAL UNTUK MENINGKATKAN EFEKTIVITAS PENGAJARAN - Ilham Zein Makbul; Eka Suhardi; Dian Wulandari (JURNAL MANAJEMEN PENDIDIKAN, 2022)
INFORMATION LITERATION AND INTERPERSONAL COMMUNICATION STRENGTHENNING EFFORTS TO IMPROVE TEACHING EFFECTIVENESSThis study was intended to find strategic and method to increase teaching effectiveness through information literation and interpersonal variables. The study utilyzed a correlational approach and SITOREM analysis which consist of two independent variables, they were information literacy and interpersonal communication, and one dependent variable that was teaching effectiveness. This research was conducted at a private vocational school in Rancabungur District in 2021. The population in the research was 155 teachers and 112 samples were selected using proportional random sampling. The method used in this study was a survey and data analysis techniques, with statistical tests of correlation and simple liniear regression and multiple linear. The results were as follow; firstly, there was a significant positive relationship between literation information (X1) and Teaching Effectiveness (Y) variables where correlation coefficient ry1 = 0,494 and determination coefficient r2 = 0,244. Secondly, There was a significant positive relationship between Interpersonal communication variable (X2) with Learning Activity (Y), where the correlation coefficient ry2 = 0.788 and determination coefficient r2 = 0.620. Thirdly, there was a significant positive relation  between Literation Information (X1) and  Interpersonal Communication variable altogether compare with Learning Effectiveness (Y) which was pointed as correlation Coefficient ry12 = 0.825 and also Determination Coefficient r2y12 = 0.681. Based on those findings, it could be concluded that Learning Effectiveness could be risen up by strengthening Information Literation and Interpersonal Communication.